Psychological profile of mothers who lost children due to violence - Vanderlei, Clarissa Fernandes; Rivera, Giovani Amado; da Silva, Jandilson Avelino (Journal of Psychological Perspective, 2023)
Grief is an amalgamation of symptoms and reactions related to significant loss. When a mother loses a child also loses its forecasts, projections, and idealizations. This study aims to psychologically analyze a sample of mothers who have lost children through violent means. They participated in ten mothers a town in Paraíba, selected through non-probability sampling for convenience. We used a socio-demographic questionnaire for the characterization data of mothers and Beck scales (Inventory Beck Depression, the Beck Anxiety and Beck Hopelessness Scale) and factorial scale of emotional adjustment / neuroticism to measure characteristics anxiety, depression, hopelessness, and emotional maladjustment. The results indicated a significant association between the variables vulnerability, anxiety, depression, inadequacy, and loss of time. The mothers had a higher incidence of anxiety symptoms. This study may contribute to the planning of a better continuous counseling the bereaved mothers.